Value of computerised tomography in children with non-specific mental subnormally. Issue 5 (May 1982) - Lingam, S; Read, S; Holland, I M; Wilson, J; Brett, E M; Hoare, R D
Abstract : Seventy-six children had computerized tomography scans as part of an investigation of mental subnormality; most of them are severely retarded and all those over age 5 years attend special schools. Seventy-two per cent of the children had normal scans. Twenty per cent showed cerebral atrophy and in only 8% was there a specific abnormality (agenesis of corpus callosum, arachnoid cyst, communicating hydrocephalus). None of these findings had any positive prognostic implication. Sedation or general anaesthesia was required for all except one child. Injection pethidine compound was used for children under age 5 years or less than 30 kg in weight, and trimeprazine orally was used for older children. The radiation exposure was high--5.6 rad per scan, which is 100 times greater than that from a posteroanterior and lateral chest x-ray film. For these reasons computerised tomography scans cannot be recommended as a routine part of the investigation of children with non-specific mental subnormality.